403 Comparative Study of Wireless Sensors Versus Type III Home Sleep Apnea Test for Home-based Diagnosis of Obstructive Sleep Apnea. (3rd May 2021) - Lee, Jong Yoon; Kim, Donghyun; Blake, Stefanida; Kalluri, Lakshmi; Walter, Jessica; Davies, Charles; Zee, Phyllis; Xu, Shuai; Power, Thomas
Abstract: Introduction: More than 22 million Americans are estimated to have obstructive sleep apnea (OSA), though this disease remains perpetually underdiagnosed. Undiagnosed OSA contributes to poor clinical outcomes, large healthcare costs and an economic burden in excess of $150 billion dollars annually. While polysomnography (PSG) is considered the gold standard to diagnose OSA home sleep apnea testing (HSAT) is now used for most patient cohorts. Wireless sensors may offer a lower cost and less burdensome approach to home testing than traditional HSAT. Methods: We performed a fully remote, national, single-arm, open-label, prospective clinical study to evaluate the performance of a wireless, two sensor experimental system (ANNETM One, Sibel Health) against a Type III HST system. A total of 154 individuals completed screening with 62 screening in as high risk for OSA using the STOP-BANG questionnaire. Ultimately 60 participants were enrolled, and 46 completed a successful home testing night wearing both the commercially available HSAT (Philips Alice NightOne Home Sleep, Koninklijke Philips N.V) and the wireless experimental system. A board-certified sleep medicine physician determined the apnea-hypopnea index (AHI) for the HSAT defined by American Academy of Sleep Medicine v2.6 guidelines. Two study investigators, blinded to the HSAT results, scored the experimental system to determine AHI based on similar guidelines. An independent study investigator conducted the final analysis of comparative performance. Participants completed a psychometric survey of their preferences, experience, and usability of the two testing systems. Results: We demonstrated a high level of agreement between the HSAT and experimental system for AHI (r2=0.81, p<0.0001). The sensitivity and specificity of the experimental system to diagnose moderate and severe OSA (AHI>15) was 85% and 95%, respectively. The experimental system had a significantly higher Systems Usability Scale score compared to HSAT (61 vs 48, p<0.0001) and more than 85% of participants preferred the experimental system. Conclusion: This study provides compelling evidence that the experimental system was highly acceptable and comparable to a currently used HSAT. Continued innovation in reliable, cost-effective, low profile technologies will be critical to address the unmet needs of sleep diagnostic testing. Support (if any): Anthem and Sibel Inc.